PLASTID TRNL INTRON VARIABILITY IN FABOIDEAE SPECIES (FABACEAE) - E. A. D’yachenko; M. A. Filyushin; E. P. Pronin; E. Z. Kochieva (Вавиловский журнал генетики и селекции)
The intron located between the first and second nucleotide of the leucine tRNA anticodon is the only representative of group I introns in higher plants. In this paper, for the first time the intron sequence of the plastid trnL gene is described in 16 legume species, and putative secondary structures of the entire intron and some of its functional domains are reconstructed. It has been found that genera of the Fabaceae family, as well as species within a single genus, are highly diverse in this sequence. Single nucleotide polymorphisms have been found in sequences of the catalytic center, believed to be highly conserved.